Addressing the Challenges: A Qualitative Analysis of Policy Implementation for Street Kid Development Program in Batam City - Aullya Rieccy Angelwiss; Lubna Salsabila; Timbul Dompak; Muhammad Akbar Hairi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This research focuses on street kid, who spend their time engaged in daily activities or wandering the streets and public places due to financial constraints in their families. Batam City, in particular, has a significant number of street children involved in various activities such as busking, selling cigarettes or newspapers, and even car cleaning at red lights. It is essential for the Batam City government, especially the Batam City Social Service, to prioritize the welfare and development of these children. This study aims to examine the policy implementation of the street children development program in Batam City, identifying the obstacles hindering the effective execution of this program. The qualitative research method, including observation and interviews, was employed to gather data. The findings reveal two key policies implemented by the Batam City Social Service: control programs and socialization and skills training. However, several challenges exist in implementing these programs, such as the lack of shelter or resting places for street children. Through this research, a deeper understanding of the policy implementation process and the barriers faced in the development of street children in Batam City can be gained